Location-tuned relaxivity in Gd-doped mesoporous silica nanoparticles - Davis, J; Huang, W; Davies, G (2012)
In tuning the sub-particle localisation of Gd(iii) binding macrocycles within a mesoporous scaffold, nanoparticle contrast agents of unprecedented relaxivity and low Gd(iii) loadings can be realised. © 2012 The Royal Society of Chemistry.